Peningkatan Prestasi Belajar Matematika melalui Penerapan Metode Numbered Heads Together (NHT) Masa Covid-19 pada Siswa Kelas VIII.A SMPN 3 Masbagik Tahun Pelajaran 2020/2021 - Apriani, Rita (MASALIQ, 2021)
This research is a classroom action research (CAR) aimed at improving Mathematics Learning Achievement which is carried out in class VIII-A students of SMPN 3 Masbagik using the Numbered Heads Together (NHT) method. The researcher conducted an action research with the aim of knowing the improvement of Mathematics Learning Achievement in grade VIII-A students of SMPN 3 Masbagik through the application of the Numbered Heads Together (NHT) method. Based on the results of research and discussion of the learning model, the Numbered Heads Together (NHT) method can increase the activity and Mathematics Learning Achievement of class VIII-A students of SMPN 3 Masbagik in the odd semester of the 2020/2021 school year. This increase can be seen from the acquisition of student activity scores and the average class value and the level of classical completeness in each cycle has increased both in cycle I and cycle II. Based on the results of data analysis in each cycle, it appears that the results from cycle I to cycle II have increased. In the implementation of learning and the results of the first cycle of data analysis, for student activities an average value of 2.50 was obtained and student activities in the second cycle obtained an average class value of 3.80 while classical completeness was obtained in cycle 1 of 59% and increased in cycle 2 by 87.5%